2007
DOI: 10.1596/1813-9450-4315
|View full text |Cite
|
Sign up to set email alerts
|

How Might Climate Change Affect Economic Growth In Developing Countries ? A Review Of The Growth Literature With A Climate Lens

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 56 publications
(45 reference statements)
1
27
0
3
Order By: Relevance
“…Although growth theories have tended to discount the relevance of volatility and shocks for long run economic performance (Lecocq and Shalizi, 2007), it has been shown that volatility can affect welfare both directly, through consumption volatility (especially problematic for the poor who find it difficult to smooth consumption in the face of a negative income shock), and indirectly through its effects on economic growth (Loayza et al, 2007).…”
mentioning
confidence: 99%
“…Although growth theories have tended to discount the relevance of volatility and shocks for long run economic performance (Lecocq and Shalizi, 2007), it has been shown that volatility can affect welfare both directly, through consumption volatility (especially problematic for the poor who find it difficult to smooth consumption in the face of a negative income shock), and indirectly through its effects on economic growth (Loayza et al, 2007).…”
mentioning
confidence: 99%
“…al., 2015, Bell et al, 2007Dessai 2003;Fay et al, 2010;Flaherty, et al, 2016;Lecocq & Shalizi, 2007). The economic impacts of CC in many cases address on global scale effects are discussed by (Stern 2007;Fay et al, 2010;Metz 2007) and some predictions of these studies have been given in Appendix A.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In practice, this means that cost–benefit analysis, in a broad sense, is likely to be the only framework within which it is meaningful to assess climate‐change policies 2–4 . Most other frameworks, such as cost‐effectiveness analysis, will only work well when the adaptation policy is the main or single government policy objective; in practice, this is rarely the case.…”
Section: Cost–benefit Analysis Of Adaptationmentioning
confidence: 99%
“…Moreover, in practice there is considerable risk that cost‐effectiveness analysis and other partial methods will lead to the adaptation measures, and their costs, implicitly being compared to the current status quo rather than to the climate change–affected “no adaptation” outcome that will prevail if nothing is done. For cost–benefit analysis, where the correct procedure is to compare the alternatives actually available, the appropriate approach is to compare adaptation measures to the outcome that will prevail in the absence of adaptation 3 . Thus, comparing adaptation measures to the current status quo is explicitly incorrect, which is not the case with other methods where there is no explicit alternative option being considered.…”
Section: Cost–benefit Analysis Of Adaptationmentioning
confidence: 99%
See 1 more Smart Citation